2021
DOI: 10.1186/s43094-021-00222-6
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of Nigerian medicinal plants: a review

Abstract: Background Cancer is currently the leading cause of death globally and the number of deaths from cancer is on the rise daily. Medicinal plants have been in continuous use over the years for the management of cancer, particularly, in most developing countries of the world including Nigeria. The use of synthetic drugs for the treatment of cancer is often accompanied by toxic side effects. Thus, the alternative use of readily available and inexpensive medicinal plants is the panacea to the toxic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 216 publications
(194 reference statements)
0
16
0
Order By: Relevance
“…Recently, numerous studies have reported the cancer therapeutic benefits of herbal medicine [ 47 , 48 , 49 , 50 ]. In the present study, a dose-dependent decrease in cell viability, proliferation, and increase in cytotoxicity in D.A root extracts (Chl, EtOAc, and MeOH), and ZnPcS 4 -mediated PDT was observed in monotherapy ( Figure 4 and Figure 5 ) as well as in combination therapy ( D.A MeOH root extract IC 50 and ZnPcS 4 -mediated PDT IC 50 ) ( Figure 6 B–D) in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous studies have reported the cancer therapeutic benefits of herbal medicine [ 47 , 48 , 49 , 50 ]. In the present study, a dose-dependent decrease in cell viability, proliferation, and increase in cytotoxicity in D.A root extracts (Chl, EtOAc, and MeOH), and ZnPcS 4 -mediated PDT was observed in monotherapy ( Figure 4 and Figure 5 ) as well as in combination therapy ( D.A MeOH root extract IC 50 and ZnPcS 4 -mediated PDT IC 50 ) ( Figure 6 B–D) in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Anticancer activities from plant bioactive components have been documented ( Sun et al., 2002 ; Surh, 2003 ; Ohiagu et al., 2021 ). Lin et al.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…odorata has been extensively studied in the last decade. N-hexane fraction of this plant has antiproliferative activity against MCF-7, MDAMB-468, and CAL51 breast cell lines, while ethanol extract of its leaves can suppress the growth of Lewis lung carcinoma cell (LLC) and HL-60 human leukemia cell lines (Ohiagu et al, 2021). The essential oil of this plant (pentacyclic triterpenoid) could decrease the viability of HepG2 cells by 90% after incubation with IC 50 value of 206 µg/ml (Prabhu and Ravi, 2012).…”
Section: Discussionmentioning
confidence: 99%